Enhancing the flotation separation of lithium adsorbents via sodium oleate-induced hydrophobic modification: Hydrophobization mechanism and field validation - Yuanliang Yang; Gang Jin; Jianqiang Tao; Chang Liu; Yawei Han; Ruoyu Ding; Yaqi Yang; Xiaolong Xiao; Xiaobing Li (Journal of Water Process Engineering, 2026)

N and S co-doped graphene-based single-atom catalysts for highly efficient nitrate reduction - Jin-Hang Liu; Yu Sun; Xiaoduo Jiang; Huixiong Jiang; Ruirui Wang; Yawei Wang; Huixian Ye; Xiudong Chen; Li-Ming Yang (Fuel, 2026)

Local versus external dust source contributions to northern China and selected downwind cities: Evidence from representative dust events in 2025 - Yawei Fan; Heqiang Du; Shengfei Yang; Yongjie Liu; Changzhen Yan; Xiao Zheng (Environmental Pollution, 2026)

Constructing atomic-scale proton channels in polymeric carbon nitride via synergistic oxygen and carbon defects for efficient CO2 photoreduction - Ruirui Wang; Yiming Wang; Jinhang Liu; Huixiong Jiang; Ran Wang; Yang Wang; Shunhang Wei; Xiaoxiang Xu; Yawei Wang (Chemical Engineering Journal, 2026)

Dual-nitrogen coordination engineering enables porous carbon-confined Pt-FeN4 atomic interfaces for durable, low-Pt PEM fuel cells - Xiaoqian Xu; Nengneng Xu; Qin Cao; Yuheng Guo; Meng Li; Yuhao Liu; Yawei Li; Guicheng Liu; Woochul Yang; Jong Min Kim; Momo Safari; Jinli Qiao (Chemical Engineering Journal, 2026)

Improved thermostability of Thermobifida fusca mannanase obtained by error-prone PCR mutagenesis - Yawei Wang; Qiang Xue; Guan Wang; Zhenggang Han; Jiangke Yang; Hairong Xiong (Biotechnology Letters, 2026)

Corrigendum to “Long-term assessment of soil wind erosion and dust emissions in China from 2000 to 2023 using an improved erodibility factor” [Aeolian Res. 76 (2026) 101049] - Yawei Fan; Heqiang Du; Shengfei Yang; Yongjie Liu; Changzhen Yan; Xiao Zheng (Aeolian Research, 2026)

Rhizosphere reactive oxygen species as a protective barrier suppress Fusarium oxysporum invasion in tomato - Yaru Zhu; Huiqiang Yang; Siqi Shen; Meng Liu; Zelin Hao; Yawei Zhou; Jinbo Liu; Hanzhong Jia (Environmental Chemistry Letters, 2026)

Exposure to multiple metals, maternal glucose homeostasis and gestational diabetes mellitus: A prospective cohort study - Hui Guo; Sijia Liu; Wenjing Li; Yongliang Feng; Ping Zhang; Changqing Li; Shuqing Bai; Yuanyuan Yang; Xi Chen; Suping Wang; Yawei Zhang; Zhijun Meng; et al. (Environmental Research, 2026)

Bisphenol A promotes esophageal carcinogenesis by activating the MMP1–PCOLCE regulatory axis and remodeling the tumor immune microenvironment - Yawei Cui; Guohang Shen; Huiling Chen; Ruoyan Wang; Chengping Zhang; Lu Han; Kaiyong Wang; Yang Chen; Junfeng Li; Xia Gao; Yupei Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Accelerated peroxymonosulfate activation via internal electron migration within Co3O4/Bi2Fe4O9 for efficient phenol degradation - Bo Liu; Hangyu Shi; Yawei Wang; Rui Liu; Shuangshuang Zuo; Qianqian Nie; Lei Yang; Hesheng Yu (Journal of Environmental Sciences, 2026)

Long-term assessment of soil wind erosion and dust emissions in China from 2000 to 2023 using an improved erodibility factor - Yawei Fan; Heqiang Du; Shengfei Yang; Yongjie Liu; Changzhen Yan; Xiao Zheng (Aeolian Research, 2026)

Investigating the impact of different abuse methods on the thermal runaway behavior of lithium batteries under high-rate charge and discharge conditions - Yajun Huang; Weifeng Xu; Xiongqi Shen; Yinquan Zhao; Yang Cao; Wei Bai; Junling Wang; Yawei Lu; Zhirong Wang (Process Safety and Environmental Protection, 2026)

LC-MS/MS analysis of polar pesticides in mango: enantiomers, docking, and retention mechanisms - Hao Yang; Yue Geng; Shu Lin; Yawei Xu; Lu Wang; Yi Peng; Yaping Xu; Xiaowei Liu; Zeying He (Food Chemistry, 2026)

Physical Activity and Depressive Mood Share the Structural Connectivity Between Motor and Reward Networks - Shiqi Di; Na Luo; Weiyang Shi; Zhengyi Yang; Jing Sui; Rongtao Jiang; Yue Cui; Zongchang Du; Jiaqi Zhang; Yawei Ma; Haiyan Wang; Congying Chu; et al. (Neuroscience Bulletin, 2026)

Parental HFPO-TA exposure induces intergenerational reproductive toxicity and DNA methylation alterations in zebrafish - Shasha Dong; Xiaohui Zhao; Xuan Ren; Jing Zhang; Zhibo Liu; Dan Yang; Ning Ji; Yawei Shi; Ya Sun; Guanghui Ding (ENGINEERING Environment, 2026)

Dual-pathway persulfate activation by mackinawite (FeS) for contaminant degradation: Overlooked role of Fe(IV) species and QSAR model - Bowen Yang; Zhihao Li; Yawei Liu; Qiang Ma; Dunqiu Wang; Longhui Zheng; Jiming Hao (Journal of Environmental Management, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Machine learning reveals molecular substructure drivers of organic contaminant translocation in crops - Haodong Lang; Yang Cui; Wen Liu; Shanshan Tang; Wei Gao; Chengyu Zhai; Jing Lu; Yawei Wang (Science of The Total Environment, 2026)

Excellent infrared radiation performance and significant energy-saving efficiency of LaAlO3 ceramics via Ca2+/Co2+ co-doping - Qinghu Wang; Yangxi Liu; Guoping Wei; Liang Huang; Xueqing Wang; Shaobai Sang; Yibiao Xu; Xiong Liang; Yawei Li; Jiangtao Li; Olena Volkova; Emad M.M. Ewais; et al. (Chemical Engineering Journal, 2026)

Brine-filled MXene “Sandwich” system for synergistically enhanced electrochemical energy storage and solar desalination - Bowen Liu; Xuedong He; Yawei Yang; Yuyao Shen; Yihong Liu; Qi Zhao; Xinye Xu; Mo Zhou; Tianyi Wang; Wenxiu Que (Chemical Engineering Journal, 2026)

Elaborating PFAS characteristics for Chinese electroplating industry by target and nontarget analysis - Bo-Xuan Zhang; Xiang-Zhou Meng; Bao-Cang Han; Zhen Zhao; Qin-Wen He; Cun-Di Ma; Qinghe Zhu; Jie Yang; Haiyan Qin; Yawei Wang (Water Research, 2025)

Efficient removal of nitrogen, phosphorus and antibiotics in freshwater aquaculture wastewater using a novel hybrid aeration biological filter - Dongyu Xia; Weina Dou; Yawei Tian; Lei Zhang; Cai Wang; Yong Wang; Jingyi Zhang; Yutong Han; Yanyan Xiao; Xu Yang; Xiang Mei (Journal of Environmental Management, 2025)

Supercritical water-assisted acid leaching for efficient copper recovery from waste circuit boards: Mechanisms, optimization, and sustainable metal extraction - Siyi Kang; Yawei Yang; Jingwei Chen; Jiaqiang E (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Self-regulated mineralization of CO2 capture products from functionalized ionic liquid into disc-shaped vaterite” [Chem. Eng. J. 522 (2025) 167956] - Yang Chen; Jingyi He; Yawei Zeng; Shaoyun He; Zhen He; Hui Hu (Chemical Engineering Journal, 2025)

Reversibility of the reproductive toxicity induced by hexafluoropropylene oxide trimer acid (HFPO-TA) in adult zebrafish (Danio rerio) - Dan Yang; Xuan Ren; Xiaohui Zhao; Shasha Dong; Xiaoying Li; Yawei Shi; Ya Sun; Guanghui Ding (Aquatic Toxicology, 2025)

Rational design of an ultra-high-gain MoS2 phototransistor enabling room-temperature detection of few-photon signals and attomolar-level immunosensing - Zhengdao Xie; Yun Hui; Wenhua Zhou; Shengxuan Xia; Yawei Lv; Liwei Ouyang; Yang Chai; Xingqiang Liu; Bei Jiang; Chang Liu; Sen Zhang; Chenchen Chu; et al. (Science Bulletin, 2025)

A Y-shaped DNA-CRISPR-Cas12a Synergy fluorescent aptasensor for ultrasensitive detection of Aflatoxin B1 - Yawei Huang; Muyue Li; Zhuang Yang; Min Wei; Zhiguang Suo (Food Bioscience, 2025)

A general pyrolysis strategy to construct rare-earth oxide-stabilized high-density Ru single atom catalysts for efficient thermocatalytic CO2 methanation - Yunxiang Tang; Yanan Zhang; Aihuan Sun; Hao Wang; Yawei Miao; Zhengyi Yang; Yunqian Tang; Qun Li; Shujiao Wang; Lingheng Kong; Yinfeng Han (Chemical Engineering Journal, 2025)

Self-regulated mineralization of CO2 capture products from functionalized ionic liquid into disc-shaped vaterite - Yang Chen; Jingyi He; Yawei Zeng; Shaoyun He; Zhen He; Hui Hu (Chemical Engineering Journal, 2025)

Stem nematode disease resistance-conferring gene identification in sweet potato using combined BSA-Seq and BSR-Seq analyses - Shouchen Qiao; Jingwei Chen; Yawei Li; Yannan Wang; Jukui Ma; Zhihe Kang; Qianqian Bian; Guozheng Cao; Guorui Zhao; Guohong Yang; Yanping Fan; Houjun Sun; et al. (Planta, 2025)

Energy-force coupling in interfacial solar vapor generation: A pathway to sustainable salt management - Yihong Liu; Yawei Yang; Bowen Liu; Qi Zhao; Yuyao Shen; Mengyuan Qiang; Yong Ma; Wenxiu Que (Desalination, 2025)

Thermo-responsive hydrogel evaporator via In-Situ chromogenic strategy for high-efficiency solar desalination with robust salt resistance - Ju Lv; Lang Pan; Yawei Zhu; Xinyue Zhang; Liujin Yang; Xiudie Wang; Xueqiong Yin (Chemical Engineering Journal, 2025)

Water erosion control through vegetation restoration: Mechanisms and contributions of vegetation components in Robinia Pseudoacacia forests - Yang Li; Yawei Hu; Jiongchang Zhao; Jianjun Zhang (CATENA, 2025)

Seasonal variation in two culture systems and genome-wide association analysis of taurine content in the foot muscles of the Pacific abalone (Haliotis discus hannai) - Ziheng Yin; Junyu Liu; Wenchao Yu; Yawei Shen; Yang Gan; Yexin Chen; Jinwei Ke; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2025)

Removal of adsorbable organic halogens generated during advanced oxidation processes using UV/sulfite - Yawei Xie; Yue Wang; Mingdi Yang; Shijie Wu; Yaozu Jin; Rui Liu; Hongyuan Liu (Journal of Water Process Engineering, 2025)

Measurement and modeling of canopy interception loss of evergreen, deciduous and mixed forests in a subhumid watershed on the Loess Plateau, China - Jiongchang Zhao; Yang Yu; Yawei Hu; Matthias Beyer; Jianjun Zhang (Journal of Hydrology, 2025)

Anti-inflammatory effect of food bioactives in inflammatory bowel disease: Role of the gut microbiome - Yawei Zhang; Lufan Zhang; Yang Dong; Yunwei Yang; Mengxing Li; Qian Chen; Dan Wang; Yuzheng Wu; Tao Wang (Food Bioscience, 2025)

Distribution, removal and potential factors affecting antibiotics occurrence in leachate from municipal solid waste incineration plants in China - Xuan Rui; Huabo Gong; Jinwen Hu; Haiping Yuan; Yawei Wang; Lixia Yang; Nanwen Zhu (Water Research, 2025)

Investigation on the inhibition mechanism of thermal runaway propagation in high-rate cycling lithium-ion pouch cells - Yajun Huang; Xiongqi Shen; Yinquan Zhao; Junling Wang; Yang Cao; Wei Bai; Yu Fan; Yawei Lu; Zhirong Wang (Process Safety and Environmental Protection, 2025)

Increased spike density and enhanced vegetative growth as primary contributors to improvement of dryland wheat yield via surface mulching - Yuwei Chai; Yawei Li; Rui Li; Lei Chang; Hongbo Cheng; Jiantao Ma; Yuqing Qin; Fanxiang Han; Changgang Yang; Yuzhang Chen; Qian Chen; Yao Zhang; et al. (Field Crops Research, 2025)

Proteomic insights from extracellular vesicles into the molecular mechanisms of health effects induced by Per- and polyfluoroalkyl substances - Yanping Li; Yadan Luo; Yang Liu; Na Li; Kai Huang; Lingxiangyu Li; Zhigang Li; Chao Han; Nali Zhu; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2025)

Mechanism investigation into static magnetic field effects on enhancing surfactin productivity by Bacillus subtilis - Yamei Jin; Sirui Chen; Qiyan Zhao; Na Yang; Yawei Ning; Xueming Xu (Food Bioscience, 2025)

Self-assembling biocompatible core-shell nanocapsules with versatile surface functionalities for precise pesticide delivery - Chunlin Yang; Zaiyu Lu; Chunhui Zhou; Xiang Yao; Yawei Tang; Xiuxia Li; Junjun Wang; Lihong Zhang (Chemical Engineering Journal, 2025)

Accurate prediction of pollution and health risks of iodinated X-ray contrast media in Taihu Lake with machine learning and revealing key environmental factors - Xinying Cheng; Yuteng Zhang; Sirui Yan; Qingsong Ji; Xiangcheng Kong; Huiming Li; Shiyin Li; Shaogui Yang; Zhigang Li; Yawei Wang; Limin Zhang; Huan He (Water Research, 2025)

Experimental investigation on seismic performance of austenitic stainless steel full-scale frames: Component response - Keyang Ning; Lu Yang; Ke Jiang; Yawei Han (Engineering Structures, 2025)

Olanzapine exposure disordered lipid metabolism, gut microbiota and behavior in zebrafish (Danio rerio) - Yawei Wang; Fu You; Zhenyi Huang; Yuan Liu; Boya Yang; Xulu Chang; Guokun Yang; Xue Tian; Shikun Feng; Xiaolin Meng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Advances in regional-scale crop growth and associated process modeling - Wenfeng Liu; Yawei Bai; Taisheng Du; Mengxue Li; Hong Yang; Shichao Chen; Chuanbin Liang; Shaozhong Kang (Science China Earth Sciences, 2025)

Recent advances in groundwater pollution research using machine learning from 2000 to 2023: A bibliometric analysis - Xuan Li; Guohua Liang; Bin He; Yawei Ning; Yuesuo Yang; Lei Wang; Guoli Wang (Environmental Research, 2025)

Transcriptome analysis of hybrid abalone (Haliotis discus hannai ♀ × H. fulgens ♂) reveals non-additive effects contributing to growth heterosis at early summer water temperature in Fujian - Zekun Huang; Yawei Shen; Xingze Wang; Qizhen Xiao; Yi Wang; Yang Gan; Zhaofang Han; Wanbo Li; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2025)

Polysaccharide-gated metal–organic framework nanoparticles for pH-triggered site-specific delivery and enhanced fungicide bioavailability - Chunlin Yang; Yawei Tang; Xiang Yao; Peijie Hu; Zaiyu Lu; Jinjing Xiao; Lihong Zhang; Haiqun Cao (Chemical Engineering Journal, 2025)

Genetic dissection of a major locus SC9.1 conferring seed color in broomcorn millet (Panicum miliaceum) - Tianpeng Liu; Kongjun Dong; Jihong He; Mei Wang; Ruiyu Ren; Lei Zhang; Yawei Li; Minxuan Liu; Tianyu Yang (Theoretical and Applied Genetics, 2025)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Interfacial evaporation and salt-blocking kinetics in Janus membrane for solar desalination - Haowei Hu; Jin Wang; Qi Zhao; Mengyuan Qiang; Qin Li; Lin Guo; Yawei Yang (Desalination, 2024)

Molecular designing of potential environmentally friendly PFAS based on deep learning and generative models - Ying Yang; Zeguo Yang; Xudi Pang; Huiming Cao; Yuzhen Sun; Ling Wang; Zhen Zhou; Pu Wang; Yong Liang; Yawei Wang (Science of The Total Environment, 2024)

Supplementation with Akkermansia muciniphila improved intestinal barrier and immunity in zebrafish (Danio rerio) - Yawei Wang; Zhenyi Huang; Zewei Gui; Boya Yang; Fu You; Guokun Yang; Xindang Zhang; Xulu Chang; Xiaolin Meng (Fish & Shellfish Immunology, 2024)

A high throughput method to assess the hypoxia tolerance of abalone based on adhesion duration - Yue Dai; Yawei Shen; Yanbo Liu; Weiwei Xia; Jiawei Hong; Yang Gan; Jie Huang; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2024)

Thyroid disrupting effects and the developmental toxicity of hexafluoropropylene oxide oligomer acids in zebrafish during early development - Xiaohui Zhao; Xianghan Meng; Dan Yang; Shasha Dong; Jianhui Xu; Dezhi Chen; Yawei Shi; Ya Sun; Guanghui Ding (Chemosphere, 2024)

Enhanced treatment of pyridine wastewater by a hybrid membrane biofilm reactor: Simultaneous biodegradation of pyridine and removal of nitrogen - Jingyi Zhang; Yawei Tian; Zhan Wang; Mengmeng Yang; Yong Wang; Han Gao; Zimiao Zhang; Yutong Han; Yanyan Xiao; Xu Yang; Xuanwei Zhao; Yue Wu; et al. (Process Safety and Environmental Protection, 2024)

Exogenous iron caused osteocyte apoptosis, increased RANKL production, and stimulated bone resorption through oxidative stress in a murine model - Zengfeng Guo; Jiawen Wu; Yawei Hu; Jianhua Zhou; Qingmei Li; Yandong Zhang; Junde Zhang; Linbo Yang; Shenghang Wang; Hao Zhang; Jiancheng Yang (Chemico-Biological Interactions, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Experimental investigation for the effect of bust pressure on hydrogen explosion venting - Yawei Lu; Rujia Fan; Zhirong Wang; Xingyan Cao; Yongjun Li; Chendi Lin; Zhuohua Yang (Fuel, 2024)

Associations of environmental cadmium exposure with kidney damage: Exploring mediating DNA methylation sites in Chinese adults - Yuan Wei; Xiaochen Wang; Qi Sun; Wanying Shi; Wenli Zhang; Xu Gao; Yawei Li; Ruiting Hao; Xiaojie Dong; Chen Chen; Kangning Cao; Weilong Jiang; et al. (Environmental Research, 2024)

Characteristics of advanced anaerobic digestion sludge-based biochar and its application for sewage sludge conditioning - Qian Chen; Xingmin Fu; Jiawei Wang; Yawei Zhao; Wei Wang; Abdul Ghaffar Memon; Huihui Zhang; Yang Wen (Bioresource Technology, 2024)

Facet-dependent transformation and toxicity of nanoscale zinc oxide in the synthetic saliva - Xiang Zhang; Yunpeng Huang; Jikun Wang; Jie Tang; Yang Mei; Nali Zhu; Zhigang Li; Lingxiangyu Li; Yawei Wang (Journal of Environmental Sciences, 2024)

Exquisite visualization of mitophagy and monitoring the increase of lysosomal micro-viscosity in mitophagy with an unusual pH-independent lysosomal rotor - Rui Yang; Wei He; Changxin Zhu; Xifeng Yang; Yawei Kuang; Tao Zhu; Jingyang Xu; Yuang Zhao; Tingwang Jiang; Yushen Liu; Mengmeng Wei (Analytica Chimica Acta, 2024)

An improved current retrieval method for ice-edge eddies from multi-sensor remote sensing image sequences - Xue Yang; Jinsong Chong; Yawei Zhao; Wenjia Zhao (International Journal of Remote Sensing, 2024)

Sustainability evaluation of urban large-scale infrastructure construction based on dynamic fuzzy cognitive map - Hongyu Chen; Shidong Cheng; Yawei Qin; Wen Xu; Yang Liu (Journal of Cleaner Production, 2024)

Proteome and gut microbiota analysis of Chinese mitten crab (Eriocheir sinensis) in response to Hepatospora eriocheir infection - Yawei Cao; Leiting Zhang; Yue Yang; Jiaying Li; Xiaoqi Luan; Xiaoli Xia; Wei Gu; Jie Du; Keran Bi; Li Wang; Qingguo Meng (Aquaculture, 2024)

Comparative transcriptome analysis and genetic dissection of vegetative branching traits in foxtail millet (Setaria italica) - Tianpeng Liu; Xueying Liu; Jihong He; Kongjun Dong; Lei Zhang; Yawei Li; Ruiyu Ren; Tianyu Yang (Theoretical and Applied Genetics, 2024)

Integrating Software FMEA and STPA to Develop a Bayesian Network-Based Software Risk Model for Autonomous Ships - Xue Yang; Yawei Zhu; Tao Zhou; Sheng Xu; Wenjun Zhang; Xiangyu Zhou; Xiangkun Meng (Journal of Marine Science and Engineering, 2023)
The autonomous shipping industry is increasingly focusing on enhancing the safety and reliability of software-based systems. Conducting a risk assessment is a requirement for demonstrating the safety equivalence of autonomous ships based on such systems to conventional vessels. Traditional risk assessment models, however, primarily focus on hardware failures, often overlooking potential software-related failures and functional inadequacies. This study proposes a framework integrating Software Failure Mode and Effects Analysis (FMEA), System–Theoretic Process Analysis (STPA), and Bayesian Network (BN) for risk identification of autonomous ship software systems. The results of a case study reveal that the framework sufficiently addresses the multifaceted nature of risks related to software in autonomous ships. Based on the findings of this study, we suggest the need for standardization of software architecture development in the autonomous ship industry and highlight the necessity for an enhanced understanding of AI-specific risks and the development of tailored risk assessment methodologies.

Low vaporization enthalpy hydrogels for highly efficient solar-driven interfacial evaporation - Qi Zhao; Yawei Yang; Benxin Zhu; Zuyi Sha; Hui Zhu; Zhixin Wu; Fahad Nawaz; Yumeng Wei; Lingdi Luo; Wenxiu Que (Desalination, 2023)

Mesopore-enhanced graphene electrodes with modified hydrophilicity for ultrahigh capacitive deionization - Ting Yang; Hongmei Zhang; Linpei Guo; Jing Wang; Zhiyuan Guo; Yawei Du; Jie Liu; Yingying Zhao; Panpan Zhang; Zhi-Yong Ji (Desalination, 2023)

Impacts of exposure to nanopolystyrene and/or chrysene at ambient concentrations on neurotoxicity in Siniperca chuatsi - Tiantian Chen; Hewei Jiang; Yawei Shen; Tingwen Cui; Zonglin Yang; Yufei Liu; Jinliang Zhao; Xiaowu Chen (Chemosphere, 2023)

Research on the risk evaluation of urban wastewater treatment projects based on an improved fuzzy cognitive map - Hongyu Chen; Jingyi Wang; Zongbao Feng; Yang Liu; Wen Xu; Yawei Qin (Sustainable Cities and Society, 2023)

Examining the impacts of implicit economic policy on urban environmental pollution: Unveiling pathways for sustainable recovery - Ya Yang; Mengru Zhou; Yawei Hou; Run Tang; Bo Liu; Yue Deng (Resources Policy, 2023)

Nanocatalyst-triggered cascade immunoassay: Multi-model immunochromatography assay for sensitive detection of Salmonella typhimurium - Xuechi Yin; Jingxin Hou; Jing Guo; Jiawei Li; Di Yang; Linpin Luo; Leina Dou; Yawei Liang; Yanru Wang; Jianlong Wang; Daohong Zhang (Chemical Engineering Journal, 2023)

Supplementation with Akkermansia muciniphila improved glucose metabolism disorder in common carp (Cyprinus carpio L.) - Guokun Yang; Aixia Jiang; Huimin Cai; Fu You; Shengkui Wu; Yanmin Zhang; Xindang Zhang; Yawei Shen; Xulu Chang; Wenpan Hu; Keke Li; Xiaolin Meng (Aquaculture, 2023)

Developmental Toxicity and Cardiotoxicity Induced by PFOS and its Novel Alternative OBS in Early Life Stage of Zebrafish (Danio rerio) - Dan Yang; Xiaohui Li; Shasha Dong; Xiaohui Zhao; Xiaoying Li; Meng Zhang; Yawei Shi; Guanghui Ding (Water, Air, & Soil Pollution, 2023)

Reaction mechanism of NO and SO2 Co-removal by calcium hydroxide - Angran Zhao; Yongqiang Han; Zhipeng Wang; Pengfei Li; Yawei Xu; Ruiming Yang; Huiling Tong (Journal of Environmental Chemical Engineering, 2023)

Efficient anti-frosting on discrete nanoclusters via spatiotemporal control of condensation frosting dynamics - Siyan Yang; Yushan Ying; Wanbo Li; Yawei Feng; Rongfu Wen; Qixun Li; Yuanbo Liu; Bingang Du; Zuankai Wang; Xuehu Ma (Chemical Engineering Journal, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Valorization of the microalgae fixing CO2 from flue gas by co-hydrothermal liquefaction with high-protein microalgae: Denitrogenation of bio-oil by ash and high energy recovery - Huihui Liu; Youjian Zhu; Wei Yang; Yawei Li; Haiping Yang; Yingquan Chen; Xianhua Wang; Hanping Chen (Fuel, 2023)

Direct absorption of atmospheric lead by rapeseed siliques is the leading cause of seed lead pollution - Junxing Yang; Yawei Yu; Chuang Ma; Hongzhong Zhang (Journal of Hazardous Materials, 2023)

Development of a synthetic transcription factor-based S-adenosylmethionine biosensor in Saccharomyces cerevisiae - Yawei Chen; Huijie Zheng; jiajia Yang; Yiting Cao; Huiyun Zhou (Biotechnology Letters, 2023)

Genome-wide association and transcriptome studies reveal the segregation mechanism of mantle markings in three-way cross hybrid abalone - Qizhen Xiao; Shihai Gong; Yawei Shen; Yisha Lu; Xinlian Lai; Wenzhu Peng; Zekun Huang; Zhaofang Han; Hongjing Ji; Yang Gan; Xuan Luo; Weiwei You; et al. (Frontiers in Marine Science, 2022)
Trait separation which often appears in shellfish progeny, has been commercially used in shellfish breeding projects. A three-way cross hybrid abalone was produced with heterosis in growth performance and thermal tolerance, and with segregation in mantle marking. However, the inheritance mechanism of mantle marking is unclear. In this study, mantle marking was demonstrated to be a qualitative trait, following simple Mendelian inheritance, through inheritance pattern analysis of the presence of black markings on the mantle in five families of three-way cross of hybrid abalone. Thermal tolerance of abalone was assessed by the Arrhenius breakpoint temperature (ABT) of cardiac performance and a correlation between mantle marking and thermal tolerance of abalone was verified. A genome-wide association study (GWAS) for mantle marking was conducted using 603,067 high-quality single nucleotide polymorphisms (SNPs) derived from 57 individuals with mantle markings (Y group) and 58 individuals without mantle markings (N group). A total of 493 SNPs that were significantly ( p < 2.32E–07) associated with mantle markings were mainly distributed on chromosome 15. In the potential significantly associated region, 80 genes, including pigmentation-related genes PTPRT , PTPRC , PNCA , and CALM4 were annotated. Transcriptome analysis of the two groups showed that the expression levels of these genes ( PTPRT , DDT-b , ATOX1 , SLC6A3 , and GSTO1 ) were significantly different, and they may play important roles in the formation of mantle markings in the three-way cross hybrid abalone. Overall, our data provide valuable information for deciphering the phenotype differences of mantle marking in three-way cross hybrid abalone and help in the molecular marker-assisted breeding in abalone.

Vector angle grouping-based solution separation for multipath/NLOS detection and exclusion with the enhancement of doppler test - Jin Chang; Xingqun Zhan; Yawei Zhai; Shizhuang Wang; Kui Lin; Rong Yang (GPS Solutions, 2022)

Bone Marrow Mesenchymal Stem Cell-Derived Exosomal microRNA-29b-3p Promotes Angiogenesis and Ventricular Remodeling in Rats with Myocardial Infarction by Targeting ADAMTS16 - Jialin Zheng; Xinjin Zhang; Wenfeng Cai; Yawei Yang; Tao Guo; Jianmei Li; Hualei Dai (Cardiovascular Toxicology, 2022)

DLGAP1-AS2 promotes estrogen receptor signalling and confers tamoxifen resistance in breast cancer - Xiaoli Liang; Yang Zhao; Zeng Fang; Nan Shao; Duanyang Zhai; Mengmeng Zhang; Liang Yu; Yawei Shi (Molecular Biology Reports, 2022)

CRISPR-Cas9-Mediated Gene Therapy in Neurological Disorders - Lihong Guan; Yawei Han; Ciqing Yang; Suxiang Lu; Jiang Du; Han Li; Juntang Lin (Molecular Neurobiology, 2022)

The neonatal PROC gene rs1799809 polymorphism modifies the association between prenatal air pollutants exposure and PROC promoter methylation - Zhiyuan Li; Meng Yang; Leizhen Duan; Yongxiang Gong; Hongxia Xia; Francis-Kojo Afrim; Hui Huang; Xiaoxue Liu; Fangfang Yu; Yawei Zhang; Yue Ba; Guoyu Zhou (Environmental Science and Pollution Research, 2022)

Identification and candidate gene mining of HvSS1, a novel qualitative locus on chromosome 6H, regulating the uppermost internode elongation in barley (Hordeum vulgare L.) - Xi Pu; Yanyan Tang; Meihao Zhang; Tao Li; Xvebing Qiu; Juanyu Zhang; Jinhui Wang; Lilan Li; Zhao Yang; Yan Su; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Preconception ambient temperature and preterm birth: a time-series study in rural Henan, China - Guoyu Zhou; Meng Yang; Jian Chai; Renjie Sun; Junxi Zhang; Hui Huang; Yawei Zhang; Qihong Deng; Lifang Jiang; Yue Ba (Environmental Science and Pollution Research, 2021)

Neurobehavioral performance of PAH exposure in male coal miners in Shanxi, China: a cross-sectional study - Fang Wang; Liuye Yang; Bin Zhang; Gaisheng Liu; Chongjian Wang; Yawei Zhang; Tong Wang (International Archives of Occupational and Environmental Health, 2020)

Multiplex genome editing using a dCas9-cytidine deaminase fusion in Streptomyces - Yawei Zhao; Jinzhong Tian; Guosong Zheng; Jun Chen; Chuanwen Sun; Zhongyi Yang; Andrei A. Zimin; Weihong Jiang; Zixin Deng; Zhijun Wang; Yinhua Lu (Science China Life Sciences, 2020)

Knockout of CTNNB1 by CRISPR-Cas9 technology inhibits cell proliferation through the Wnt/β-catenin signaling pathway - Lihong Guan; Shaoyi Zhu; Yawei Han; Ciqing Yang; Yanli Liu; Liang Qiao; Xiaoying Li; Han Li; Juntang Lin (Biotechnology Letters, 2018)

The differential expression of novel circular RNAs in an acute lung injury rat model caused by smoke inhalation - Zhiqiang Ye; Xuhui Liu; Yuewu Yang; Xianling Zhang; Ting Yu; Shigeng Li; Yawei Feng; Gangjian Luo (Journal of Physiology and Biochemistry, 2018)

Adiponectin Suppresses T Helper 17 Cell Differentiation and Limits Autoimmune CNS Inflammation via the SIRT1/PPARγ/RORγt Pathway - Kai Zhang; Yawei Guo; Zhenzhen Ge; Zhihui Zhang; Yurong Da; Wen Li; Zimu Zhang; Zhenyi Xue; Yan Li; Yinghui Ren; Long Jia; Koon-Ho Chan; et al. (Molecular Neurobiology, 2017)

Polymorphisms in complement genes and risk of preeclampsia in Taiyuan, China - Weiwei Wu; Hailan Yang; Yongliang Feng; Ping Zhang; Shuzhen Li; Xin Wang; Tingting Peng; Fang Wang; Bingjie Xie; Pengge Guo; Mei Li; Ying Wang; et al. (Inflammation Research, 2016)

Concentrations and Seasonal Variation of Ambient PM2.5 and Associated Metals at a Typical Residential Area in Beijing, China - Jing Yang; Qiang Fu; Xiaoshuang Guo; Baolin Chu; Yawei Yao; Yanguo Teng; Yeyao Wang (Bulletin of Environmental Contamination and Toxicology, 2015)

Multilayer Pressure Containment Model and its Application in Deep Well Fractured Formation - Pei Yang; Mian Chen; Yan Jin; Bing Hou; Yunhu Lu; Chuan Liang; Qianqian Zhu; Yawei Li (Rock Mechanics and Rock Engineering, 2013)

Family history of malignancies and risk of breast cancer: prospective data from the Shanghai women’s health study - Briseis A. Kilfoy; Yawei Zhang; Xiao-Ou Shu; Yu-Tang Gao; Bu-Tian Ji; Gong Yang; Hong Lan Li; Nathaniel Rothman; Wong-Ho Chow; Wei Zheng (Cancer Causes & Control, 2008)